Meriones chengi Wang 1964 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Meriones chengi Wang, 1964. Acta Zootax. Sin., 1:9. TYPE LOCALITY: China, Sinkiang, Turfan, 42° 55' N., 89° 06' E. DISTRIBUTION: Known only from the type locality. COMMENT: Possibly a form of meridianus; but should be regarded as distinct until comparisons are possible (DML). Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 3), pp. 392-476 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 424, DOI: 10.5281/zenodo.7353031